Correlation between self-reported exercise participation and blood pressure at rest among undergraduate students of Ignatius Ajuru University of Education, Port Harcourt, Rivers State - Kpai, Tonubari (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
Hypertension is a growing concern among young adults particularly university students due to the increasing prevalence of sedentary lifestyles and reduced physical activity. This study investigated the correlation between self-reported exercise participation and blood pressure at rest among undergraduate students of Ignatius Ajuru University of Education, Port Harcourt, Rivers State. Seven research questions and two hypotheses guided the study. The study design was quasi-experimental. The study population comprised all undergraduate students of the institution and a sample of two hundred students was recruited using convenience sampling. Data on self-reported exercise participation was collected using a self-structured questionnaire with 0.71 coefficient reliability while blood pressure in mmHg was measured with a digital device. Data was analysed using frequency counts, percentages, mean and standard deviation while hypotheses were tested using an Independent Sample t-test and PPMC at 0.05 alpha level of significance. The findings showed that the mean age of participants was 23.79±3.76years with more females than males in the study. The majority of the students reported participation in various forms of exercise however, in spite of the impressive rate of participation, the duration of exercise sessions was low. The mean systolic blood pressure was 126.28mmHg among males and 118.53mmHg among female students; the mean diastolic blood pressure was 84.50mmHg among males and 83.02mmHg among female students. The tested hypotheses revealed exercise was significant and negatively correlated with systolic (r=-0.311; p=0.000) and diastolic (r=-312; p=0.003) blood pressure. Also, there was a significant difference (t= 2.997; p= 0.003) in blood pressure based on gender among the undergraduate students, with the males having a higher mean incidence of elevated blood pressure than the females. Students should be encouraged to prioritise physical exercise while university management is encouraged to provide needed opportunities for students to incorporate exercise into their daily routines to promote healthy and all-round wellness.